The Superior Anti-caries Efficacy of Fluoride Toothpaste Containing 1.5% Arginine - Cummins, D (The Journal of clinical dentistry, 2016)
Innovation in the dental caries area and the development of new superior efficacy treatments to prevent dental caries are as important today as they have ever been, because caries remains a highly prevalent disease globally. Appropriately designed and well-conducted, randomized clinical trials (RCTs) are best-in-class evidence of the effectiveness of a new intervention in medicine and dentistry, and traditional two- to threeyear caries clinical trials are currently the gold standard for proof of superior caries prevention efficacy. Based upon a detailed understanding of plaque metabolism and the importance of pH rise factors in the prevention of caries, a novel toothpaste containing 1.5% arginine, an insoluble calcium compound, and fluoride has been developed, and its superior efficacy compared to toothpaste with fluoride alone has been validated in an unprecedented series of ten RCTs. The results of these RCTs are summarized, and some of the details of the procedures used in the studies are clarified in order to provide an opportunity for objective assessment of their quality. In addition, the results of studies which explored the mechanism of action of this toothpaste are summarized. The arginine-containing fluoride toothpaste offers its users the opportunity to supplement mechanical plaque control with a new technology that helps maintain the natural oral flora in a state that is compatible with health, so as to retain the beneficial effects of the natural flora while significantly reducing the risk of dental caries compared to conventional fluoride toothpaste.